Can extreme experiences enhance creativity? The case of the underwater nightclub - Richardson, Daniel C.; Tagomori, Hosana; Devlin, Joseph T. (Frontiers in Psychology, 2022)
Creativity is a valuable commodity. Research has revealed some identifying characteristics of creative people and some of the emotional states that can bring out the most creativity in all of us. It has also been shown that the long-term experience of different cultures and lifestyles that is the result of travel and immigration can also enhance creativity. However, the role of one off, extreme or unusual experiences on creativity has not been directly observed before. In part, that may be because, by their very nature, such experiences are very difficult to bring into the laboratory. Here we brought the tools and empirical methods of the laboratory into the wild, measuring the psychological effects of a unique multisensory experience: an underwater nightclub. We showed – with fully randomised and experimentally controlled conditions – that such an experience boosted measures of divergent thinking in participants. This demonstrates that one element of creativity can be directly enhanced by unusual situations, and that experimental tools of psychology can be used to investigate a range of consumer experiences.